Cloud Computing Economic Impact Modelling Using General Equilibrium Models - POPÎRLAN, Cristina; POPÎRLAN, Claudiu-Ionuț; STOIAN, Gabriel (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).32, 2020)
This study offers a general view over Cloud computing in Europe and an evaluation of the probable impact cost-wise and its benefits. We also give a model to analyze the cost and gain based on a vast analysis of specialty literature, data sets and available statistics. The main scope is to evaluate the cloud computing market, including micro and macro-economic analysis as well as the impact it has over the European Union’s environment. Various economic sectors are inspected in order to establish the average benefits and costs that involve embracing Cloud computing.